Novel regulators of hepatic macrophages in liver fibrosis - Tang, Xiangjun; Bai, Meiwen; Du, Xianhong; Wang, Hong; Liu, Meifang; Fu, Xiaoyan; Zhang, Hongxia; Liang, Shujuan; Wang, Liyuan (Frontiers in Immunology, 2025)
Liver fibrosis is a common pathological process resulting from liver damage and subsequent inflammatory responses in various chronic liver diseases, leading to persistent structural and functional abnormalities in the liver. It can further progress to liver cirrhosis and hepatocellular carcinoma. Currently, no effective treatments are available for liver fibrosis, except for liver transplantation. Hepatic macrophages play essential roles in both the development and regression of liver fibrosis. Understanding the mechanisms by which hepatic macrophages regulate liver fibrosis could identify new therapeutic targets. In this review, we aim to summarize recent discoveries regarding the specific molecular mechanisms underlying the progression of liver fibrosis over the past 5 years, with a special focus on monocyte recruitment and macrophage polarization or differentiation, as well as their roles in disease progression.